Türkiye turizmi sözlü tarih araştırması görüşme metinleri (İstanbul)
10 c. (xx, 865 s. ; xx, 723 s. ; xx, 558 s. ; xx, 643 s. ; xxii, 824 s. ; xx, 548 s. ; xx, 433 s. ; xxiv, 908 s. ; xxii, 769 s. ; xvi, 960 s. )